DESIGN OF THE CARD GAME "NUTRITION IN & OUT" AS A MEDIA TO BALANCE FOOD INTAKE AND PHYSICAL ACTIVITY IN CHILDREN AGED 10-12 YEARS - Annisa Oktadea Marselina; Sri Retnoningsih (SNADES, 2025)
School-age children are in a growth phase leading to adolescence, requiring optimal nutritional intake to support physical, mental, and intellectual development. However, global challenges such as increased consumption of unhealthy foods and reduced physical activity due to excessive technology use can impact children’s lifestyles. This study aims to provide education about healthy lifestyles based on the concept of balanced nutrition guidelines so that children can understand the importance of fulfilling nutritional needs that are beneficial for their bodies. The methods employed in this study included literature reviews, observations, and interviews to collect data, which were then analyzed using a SWOT approach. The results of the analysis were used as the basis for the process of designing educational media using a cyclic strategy, resulting in new, effective media in the form of an interactive card game for school-age children. By using a game concept that has challenging missions and action cards, complemented by illustrations and explanations tailored to the characteristics of school children, it encourages children’s understanding of the body’s need for balanced food intake and physical activity. The results of the study indicate that the designed card game is effective in providing children with an understanding of the concept of balanced nutrition and a healthy lifestyle. With this game, it is hoped that children can start to get used to a healthier lifestyle in accordance with nutritional guidelines to avoid various infectious diseases and can grow more optimally for the future.